Corneal Treatment, Repair, and Regeneration: Exosomes at Rescue - Brooke T. Robbins; Kate A. Montreuil; Neloy Kundu; Prashant Kumar; Vibhuti Agrahari (MDPI AG, 2024)
Exosomes are extracellular vesicles within the nanosized range that play roles in intercellular communication and thus have certain biological activities. The secretory signaling communication mechanism is an efficient way of exchanging information between cells and has been investigated as nature's therapeutic drug carriers. This review will summarize the potential of exosomes as therapeutic tools and drug delivery vehicles for corneal pathologies. The cornea is an avascular ocular tissue, and its healing is a complex process including cell death and migration, cell proliferation and differentiation, and extracellular matrix remodeling. Here, we discussed the structure, barrier, phases, and healing cascade of cornea. We briefly reviewed the immunogenicity and toxicity of exosomes and role of exosomes in preserving cornea. Additionally, we provided combining exosome strategies with hydrogels, gene and stem cells therapy focused on corneal treatment, repair, and regeneration.